Competition Between Entropy and Energy in Network Glass: The Hidden Connection Between Intermediate Phase and Liquid-Liquid Transition - Toledo-Marín, J. Quetzalcóatl; Yan, Le (Frontiers in Materials, 2019)
In network glass including chalcogenides, the network topology of microscopic structures can be tuned by changing the chemical compositions. As the composition is varied, an intermediate phase (IP) singularly different from the adjacent floppy or rigid phases on sides has been revealed in the vicinity of the rigidity onset of the network. Glass formers in the IP appear to be reversible at glass transition and strong in dynamical fragility. Meanwhile, the calorimetry experiments indicate the existence of a first-order liquid-liquid transition (LLT) at a temperature above the glass transition in some strong glass-forming liquids. How are the intermediate phase and the liquid-liquid transition related? Recent molecular dynamic simulations hint that the intermediate phase is thermodynamically distinct that the transitions to IP as varying the chemical composition in fact reflect the LLT: out of IP, the glass is frozen in vibrational entropy-dominated heterogeneous structures with voids; while inside IP, energy dominates and the microscopic structures of liquids become homogeneous. Here we demonstrate such first-order thermodynamic liquid-liquid transition numerically and analytically in an elastic network model of network glass and discuss possible experimental approaches to testify the connection.